2014
DOI: 10.1016/j.addr.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-containing polymers for localized, sustained drug delivery

Abstract: Many currently used antibiotics suffer from issues such as systemic toxicity, short half-life, and increased susceptibility to bacterial resistance. Although most antibiotic classes are administered systemically through oral or intravenous routes, a more efficient delivery system is needed. This review discusses the chemical conjugation of antibiotics to polymers, achieved by forming covalent bonds between antibiotics and a pre-existing polymer or by developing novel antibiotic-containing polymers. Through con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 54 publications
1
76
0
2
Order By: Relevance
“…[6] 3 Curcumin (Cur) is extracted from turmeric as food additive or traditional medicine for centuries in China and India. It has been found that Cur has very low toxicity or even nontoxicity on healthy cells, but selective toxicity on many cancer cells.…”
mentioning
confidence: 99%
“…[6] 3 Curcumin (Cur) is extracted from turmeric as food additive or traditional medicine for centuries in China and India. It has been found that Cur has very low toxicity or even nontoxicity on healthy cells, but selective toxicity on many cancer cells.…”
mentioning
confidence: 99%
“…1 So far, many different types of antimicrobial polymers have been devised, 2-7 including antimicrobial cationic polymers, 8,9 biocide-released polymers 10,11 and so forth. Among them, antimicrobial cationic polymers have attracted most of the attentions in this field, because compared with antibiotics, antimicrobial cationic polymers may not induce serious microbial drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, the antibiotic‐conjugated polymeric systems can be fabricated via pendant conjugation of antibiotics to the backbone chain of polymer or the polymerization of antibiotic‐containing small molecule with polymerizable moieties, as depicted in Figure . For example, penicillin G and penicillin V moieties were conjugated to the end group of poly(2‐oxazoline)s, resulting in higher stability and antibacterial activity in the existence of penicillinase.…”
Section: Biodegradable Polymeric Nanosystems Containing Antibioticsmentioning
confidence: 99%